HLA-DRB1 ALLELE DISTRIBUTION IN HEALTHY INDIVIDUALS CLASSIFIED BASED ON MIZAJ (TEMPERAMENT) OF UNANI SYSTEM OF MEDICINE - MULLA, GHAZALA; SHAH, TEJAS; JOSHI, KALPANA; AHMED, JALIS; QURESHI, FARHAN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Assessment of Mizaj of 500 healthy individuals between the age group of 25and 40 years of the age group of either gender was carried out by validated Unani questionnaire and Sheldon’s somatotype. The present study was designed to investigate if the frequency of HLA-DRB1 alleles in the healthy adult population has any association with four Mizaj. Methods: Mizaj of the healthy individuals (n=500) was assessed by a validated Unani questionnaire based on 10 parameters related to phenotypic and psychological entities known as Ajnas-e-Ashra. Mizaj of the same subjects was further assessed by Sheldon’s somatoplot. Polymerase chain reaction-sequence-specific typing method was used for human leukocyte antigen (HLA) genotyping of 180 healthy volunteers. Conclusion: An expected correlation between HLA-DRB1 alleles and Mizaj types is observed. Five single-nucleotide polymorphisms (p<0.05) were significantly associated with different Mizaj. The study suggests that the Mizaj classification of the Unani system of medicine has a genetic basis. This study would be one step toward a personalized approach as per the Mizaj of an individual to disease proneness, lifestyle modification, and medicine.